ANALISA PEMIDANAAN PELAKU TINDAK PIDANA PENGGELAPAN DI PARIGI MOUTONG (PUTUSAN NOMOR 85/PID.B/2020/PN PRG) - Yoga Gunandy Dananjaya; Maria Silvya E. Wangga (Reformasi Hukum Trisakti, 2021)
This research relates to the punishment of several acts of embezzlement known as concurrence of acts or concursus. The problems are: is there a combination of crimes in this crime of embezzlement in decision number 85/Pid.B/2020/PN.PRG. and what are the criminal sanctions against the perpetrators of the crime of embezzlement according to the Criminal Code (KUHP)? The research is a normative juridical and analytical descriptive. The results of the research and discussion are that in the case of the Parigi District Court decision Number 85/Pid.B/2020/PN PRG there is a combination of criminal acts in the form of concurcus realis. The form of criminal sanctions for the crime of embezzlement in the decision of the Parigi District Court Number 85/Pid.B/2020/PN PRG for the type of combined criminal acts concurrently/concurcus realis adheres to the criminal system of the heaviest punishment system where the judge only imposes the most severe punishment with added weighting. This research suggests that the Panel of Judges of the Parigi District Court pay more attention to the applicability of the principles of criminal law, especially the arrangements regarding the combination of criminal acts or concursus realis and the forms of criminal sanctions that are applied.